Bundling of animal health services increases access to quality services to more than 90% of pastoralists - CGIAR Research Program on Livestock (2017)
Access to animal health services is one of the most important factors in improving livestock productivity. We piloted bundling of additional services by public and private sectors during vaccination campaigns. In two counties in Kenya, Garissa and Marsabit, it's now routine for the government to invite private sector actors to provide additional services while the government provides vaccinations. This has saved the government money, increased business opportunities for the private sector, and provided quality services to pastoralists at affordable prices.